DARI HAK ATAS LINGKUNGAN HIDUP MENUJU KEWAJIBAN ANTI-KRIMINALISASI: REKONSTRUKSI KEWAJIBAN NEGARA TERHADAP PEMBELA HAK ASASI MANUSIA MASYARAKAT ADAT - Yasser Arafat (Faculty of Law-Universitas Bandar Lampung, 2026)
The recognition of the right to a clean, healthy, and sustainable environment has strengthened the status of the environment within the human rights regime, yet it has not fully addressed the criminalisation of communities that defend ecosystems. This article aims to reconstruct state responsibility towards Indigenous human rights defenders through the concept of anti-criminalization duties. The study employs a qualitative design based on secondary data and a doctrinal-conceptual legal research approach integrating international human rights law, environmental law, the rights of Indigenous Peoples, environmental justice, and critical legal analysis. The article finds that criminalisation operates across a spectrum of repression encompassing criminal prosecution, SLAPP, judicial harassment, administrative repression, securitization, symbolic delegitimation, and restrictions on participatory space. Its underlying mechanisms include the unequal distribution of ecological benefits and burdens, failures to recognise Indigenous territories, the weakening of FPIC, the juridification of ecological conflicts, and inadequate due diligence and corporate accountability. The originality of this article lies in shifting the analysis from the recognition of environmental rights towards state obligations to prevent the misuse of law against Indigenous human rights defenders. Its contribution is to formulate anti-criminalization duties as an evaluative framework for assessing whether states have respected, protected, and fulfilled rights in conflicts involving the environment, conservation, extraction, infrastructure, and energy transition.